Contesting a legendary legacy: A century of reflection on Raymond Dart and the Taung skull - Christa Kuljian (South African Journal of Science)
In 1925, Raymond Dart published his description of the Taung Child skull, which he named Australopithecus africanus, thereby making a pivotal contribution to the field of palaeoanthropology. While recognising Dart’s central role in the field, this paper reviews the historiography of two aspects of Dart’s legacy. First, this paper explores how, over time, Dart’s telling of the story of the Taung fossil obscured the role of geologist Robert Young and promoted the myth of ‘one man, one fossil’, rather than the reality that all scientific efforts reflect the work of a team. Then the paper shifts to review Dart’s belief in race typology, and his disturbing anthropological practices. These beliefs and practices were not questioned in the era of racial segregation and apartheid, and they carry painful legacies into the fields of anatomy, anthropology and palaeoanthropology. Dart’s legacy was upheld during his lifetime and was further protected for another 25 years after his death by Dart’s protégé and successor, Phillip Tobias. However, critical reflection on Dart’s legacy of scientific racism began in the 1990s and continues today. Dart’s important contribution to palaeoanthropology, the description of the Taung skull, continues to eclipse other more negative aspects of his legacy. This paper reviews scholarly writing on Dart’s overall career, confirms this legacy of scientific racism, and argues that it stands alongside his legendary legacy of the description of the Taung Child skull.